Improvement of freight transportation technologiy in the multimodal railway-water transport - Valeriy V. Zubkov (Вестник Научно-исследовательского института железнодорожного транспорта, 2019)
Analysis of arrangement of the local operation during freight transportation by the multimodal railway-water transport to Tobolsk river port of the Ob-Irtysh bassin is presented. Dynamics of growth of construction cargo loading and increase of the volumes of their transportation to the port enhance the working capacity of Sverdlovsk railroad, which increases the loading level of its processing and carrying capacities. It should be noted that the level of quality and reliability of such transportation is reduced in the period of the transport infrastructure repair, when the number of the freight trains temporarily removed from operation is grown at the approaches to the port railway station. The search for the possible solutions of arranging the local operation was conducted at the route limited in the carrying and processing capabilities, in particular at the interaction of two types of transport: railway and inland water transport. Effective solutions for automation of the processes of adaptive approval of the volume of transported cargo are proposed, as well as the methods and options of their transportation at all stages of transportation services, forecasting and planning of the regional freight transportation as a part of the inter-industry transportation. The “Electronic service of the complex transportation services” system is presented, which provides for selection of the best option of effect on the main quality criteria of the regional freight transportation and ensures self-arrangement and self-support of the process when its conditions are changed under the impact of external and internal factors. The system calculates the economically feasible mode of transportation, performs adaptive approval of the volumes of transported cargo at all stages of the technological cycle of rendering complex transportation services. The system provides for information and analytical support of the functions of planning, arrangement of local operation, and collection, analysis, and processing of statistical data. Methods of the system construction are used for control of the transportation services when arranging the car traffic volume of inert cargo making the forecast of their delivery. The “Electronic service of the complex transportation services” system has passed the state registration.